2019
DOI: 10.1667/rr15440.1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Effects of 1-Palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) on Hematopoietic Acute Radiation Syndrome after Total-Body Ionizing Irradiation in Mice

Abstract: Acute radiation syndrome (ARS) occurs as a result of partial-or whole-body, high-dose exposure to radiation in a very short period of time. Survival is dependent on the severity of the hematopoietic sub-syndrome of ARS. In this study, we investigated the mitigating effects of a lipid molecule, 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG), on the kinetics of hematopoietic cells, including absolute neutrophil count (ANC), red blood cells (RBCs) and platelet counts, in mice after gamma-ray total-body irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Previously, PLAG has been demonstrated in various inflammatory diseases, such as hepatitis, asthma, rheumatoid arthritis, and oral mucositis [26,27,28,29]. Recently, we showed that administration of PLAG effectively mitigates hematopoietic acute radiation syndrome of mice following a lethal dose of gamma-ray irradiation [30]. Besides, PLAG effectively reduced the incidence of gemcitabine-induced neutropenia by attenuating IL-8-induced neutrophil extravasation in clinical and nonclinical settings [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, PLAG has been demonstrated in various inflammatory diseases, such as hepatitis, asthma, rheumatoid arthritis, and oral mucositis [26,27,28,29]. Recently, we showed that administration of PLAG effectively mitigates hematopoietic acute radiation syndrome of mice following a lethal dose of gamma-ray irradiation [30]. Besides, PLAG effectively reduced the incidence of gemcitabine-induced neutropenia by attenuating IL-8-induced neutrophil extravasation in clinical and nonclinical settings [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The hematopoietic system is one of the systems most sensitive to IR, and it is vulnerable to radiation (Kim et al, 2019). Hematopoietic stem cells are very sensitive to radiation, and they are sharply decreased after radiation, which makes the source of mature blood cells in peripheral blood deficient.…”
Section: Discussionmentioning
confidence: 99%
“…The hematopoietic system is sensitive to radiation (Kim et al., 2019). The decrease of the number of WBC in the peripheral blood and the contents of DNA in bone marrow can reflect the damage degree of hematopoietic system (Shao et al., 2018).…”
Section: Resultsmentioning
confidence: 99%